Synthesis and Characterization of Biodegradable Blend based on LDPE/cassava stem nanofiber cellulose - L Lismeri; N Herdiana; D Kameswara; P S Anungputri; Y Darni; Azhar Azhar (Universitas Muslim Indonesia, 2021)
Conventional plastic becomes trend topic due to its long degradation time and needs attention related to environmental problem. One type of plastic that is difficult to be degraded is LDPE. Some of the efforts done is to synthesize plastics with organic material so that it becomes biodegradable plastic. Cellulose is an organic material that is abundant in nature and can be used as a filler. This research aims to synthesis the biodegradable plastic films composted by nanocellulose – LDPE. Mechanical (UTM), water resistance and degradation test has been done. The properties of the biodegradable blend still meet the commercial LDPE standart. Even though the biocomposite based on LDPE-nanofiber cellulose can not totally degradable but it is can be used as a solution to reduce the degradation time of a plastic waste.